2017
DOI: 10.3892/or.2017.5912
|View full text |Cite
|
Sign up to set email alerts
|

Sanggenon C induces apoptosis of colon cancer cells via inhibition of NO production, iNOS expression and ROS activation of the mitochondrial pathway

Abstract: Sanggenon C is a well-known, major active agent of the flavonoid derivative of benzopyrone with valuable biological properties, including anticancer, anti-inflammatory, antimicrobial, antiviral, antithrombotic, and immune-modulatory activities. In this study, we investigated the molecular mechanisms by which sanggenon C mediated the induction of cell death in colorectal cancer cells (CRC). Treatment of colorectal cancer cells (LoVo, HT-29 and SW480) with sanggenon C (0, 5, 10, 20, 40 and 80 µM) resulted in inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…Mitochondrial membrane permeabilization (MMP) is closely associated with cancer cell death. Mitochondrial Ca 2+ overload drives ROS generation, triggering MMP and release of pro-apoptotic factors, leading to cell apoptosis and death ( 21 ). Furthermore, high concentrations of NO derived from iNOS inhibit the expression of Bcl-2, activate caspase and subsequently promote the release of cytochrome c , leading to cell death ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial membrane permeabilization (MMP) is closely associated with cancer cell death. Mitochondrial Ca 2+ overload drives ROS generation, triggering MMP and release of pro-apoptotic factors, leading to cell apoptosis and death ( 21 ). Furthermore, high concentrations of NO derived from iNOS inhibit the expression of Bcl-2, activate caspase and subsequently promote the release of cytochrome c , leading to cell death ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary study found that water extract and ethanol extract of Cortex Mori could stimulate MC3T3-E1 cells and inhibit osteoclast in vitro. Sanggenon C (C 40 H 36 O 12 , Figure 1 ), which is a main active flavanone originating from Cortex Mori, has been found to possess antioxidant, anti-inflammatory, and antitumor properties [ 7 , 8 , 9 , 10 , 11 , 12 ]. There was evidence that the increase reactive oxygen species (ROS) level and the inflammatory response were shown to be directly related to the osteoporosis [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…NO and ROS was free radicals that are synthesized by iNOS [14]. iNOS and COX-2 are major inflammatory factors.…”
Section: Resultsmentioning
confidence: 99%